Effectiveness of exercises intensity in improving cardiorespiratory fitness and body fat percentage among obese adults: a systematic review and meta-analysis / Nurul Najwa Aminul Mahzan ... [et al.] - Aminul Mahzan, Nurul Najwa; Ilias, Noor Fatihah; Abdul Razak, Mohd Noorazam; Ismail, Hashbullah (Faculty of Sport Science and Recreation, Universiti Teknologi MARA, 2024)
Exercise, as a non-pharmacological strategy, has demonstrated positive effects in managing cardiorespiratory fitness and adiposity among obese individuals. However, the comparative effectiveness of Moderate-Intensity Continuous Training (MICT) and High-Intensity Interval Training (HIIT) remains inconclusive. This study aimed to identify the most efficient exercise intensity for improving cardiorespiratory fitness and reducing body fat percentage in obese individuals. This review only included subjects who had a mean BMI of ≥30 kg/m2, percentage body fat >30kg, aged between 18 and 60 years old and only consisted of intervention of exercises alone without caloric restriction. The study employed HIIT intervention at 85% Heart Rate Reserves (HRR) and MICT at 60% HRRA systematic search of electronic databases was conducted from 1970 to October 2022, yielding twenty eligible studies. The PRISMA flowchart guided study selection, meanwhile the quality of included studies was assessed using TESTEX criteria. The results of the study indicated no significant difference between HIIT and MICT in improving cardiorespiratory fitness (WMD = 0.27; 95% CI: 0.01 to 0.53; P = 0.04; I²: 25%) or percentage body fat (WMD: 0.23; 95% CI: -0.53 to 0.07; P = 0.13; I²: 67%) among obese adults. Despite small changes, both exercise modalities demonstrated improvements. Therefore, health practitioners are encouraged to prescribe exercises tailored to individual preferences, as HIIT and MICT provide equivalent effects. This study contributes to the understanding of exercise interventions for managing obesity-related health outcomes.